Analyzing long-term reliability and potential of organic eutectic Phase Change Material as thermal batteries - Jacob, Jeeja; Paul, John; Pandey, A. K.; Selvaraj, Jeyraj; Nasrudin, Abd Rahim; Samykano, Mahendran; Kadirgama, Kumaran (Elsevier Ltd, 2023)
The current century is experiencing a notable and expeditious transition toward environmentally sustainable and renewable energy sources to mitigate the effects of climate change. Solar energy is a widely utilized renewable energy source due to its abundance and cleanliness despite its disparate distribution. Integrating Latent Heat Energy Storage (LHES) components into solar energy storage systems can potentially mitigate anomalies in solar radiation. Phase Change Materials (PCMs) are widely regarded as the most commonly utilized substance for Thermal Energy Storage (TES). The thermal management potential of a TES system is substantially hindered due to the limited thermal conductivity of PCMs. The present study attempts to create a binary eutectic PCM for employment in desalination systems, electronic thermal management, and other medium-temperature applications. The melt blending approach was used to synthesize a Binary Eutectic PCM (BEPCM), mixing paraffin and palmitic acid, and the composite's thermophysical properties were evaluated. The stability of BEPCM was confirmed by using the techniques of Thermogravimetric Analysis and Fourier Transform Infrared Spectroscopy. The synthesized BEPCM's thermal conductivity was 0.256 W⸱m−1⸱K−1 (an increase of 11.3 % above palmitic acid). The melting point and latent heat values were found to be 55 °C and 160 J/g. An in-depth morphological and thermophysical analysis following 4000 thermal cycles validated the EPCM's long-term reliability. Thus, a cost-effective, robust, and reliable PW-PA-based BEPCM was manufactured. The composite benefits TES systems operating at moderate temperatures due to their improved thermophysical capabilities.